AMTAC-19, a Spiro-Acridine Compound, Induces In Vitro Antitumor Effect via the ROS-ERK/JNK Signaling Pathway - Valgrícia Matias de Sousa; Sâmia Sousa Duarte; Rafael Carlos Ferreira; Natália Ferreira de Sousa; Marcus Tullius Scotti; Luciana Scotti; Marcelo Sobral da Silva; Josean Fechine Tavares; Ricardo Olímpio de Moura; Juan Carlos Ramos Gonçalves; Marianna Vieira Sobral (Molecules)
Colorectal cancer remains a significant cause of mortality worldwide. A spiro-acridine derivative, (E)-1′-((4-bromobenzylidene)amino)-5′-oxo-1′,5′-dihydro-10H-spiro[acridine-9,2′-pyrrole]-4′-carbonitrile (AMTAC-19), showed significant cytotoxicity in HCT-116 colorectal carcinoma cells (half maximal inhibitory concentration, IC50 = 10.35 ± 1.66 µM) and antioxidant effects after 48 h of treatment. In this study, Molegro Virtual Docker v.6.0.1 software was used to investigate the interactions between AMTAC-19 and the Extracellular Signal-Regulated Kinase 1 (ERK1), c-Jun N-terminal Kinase 1 (JNK1), and p38 Mitogen-Activated Protein Kinase α (p38α MAPK). In vitro assays were conducted in HCT-116 cells to evaluate the effect of AMTAC-19 on the modulation of these proteins’ activities using flow cytometry. Furthermore, the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay in the presence or absence of ERK1/2, JNK, and p38 MAPK inhibitors was used to evaluate the involvement of these enzymes in AMTAC-19 cytotoxicity. ROS production was assessed using the 2,7-dichlorodihydrofluorescein diacetate (DCFH-DA) assay at various incubation times (30 min, 1 h, 6 h, 12 h, and 24 h), and the MTT assay using N-acetyl-L-cysteine (NAC) was performed. In silico results indicated that AMTAC-19 interacts with ERK1, JNK1, and p38α MAPK. Additionally, AMTAC-19 activated ERK1/2 and JNK1 in HCT-116 cells, and its cytotoxicity was significantly reduced in the presence of ERK1/2 and JNK inhibitors. AMTAC-19 also induced a significant increase in ROS production (30 min and 1 h), while NAC pretreatment reduced its cytotoxicity. These findings support AMTAC-19′s in vitro antitumor effect through ROS-dependent activation of ERK and JNK pathways.